1994
DOI: 10.1021/bi00175a024
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase-mediated processing of fibronectin by endothelial cell monolayers

Abstract: We studied the interaction of [125I]fibronectin with human umbilical vein endothelial cells. Endothelial cell monolayers cross-linked [125I]fibronectin which had been preadsorbed to gelatin-coated dishes. The cross-linking of the substrate-immobilized [125I]fibronectin was mediated by cell-associated tissue transglutaminase and occurred more rapidly during the first 30 min after endothelial cell seeding but also continued for several hours after the cells were fully spread. The processing of the [125I]fibronec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
93
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 44 publications
7
93
0
1
Order By: Relevance
“…It has been suggested that TG2-mediated ECM crosslinking in HUVEC and the endothelial-like cell line ECV304 contributes to basement membrane assembly and cell adhesion. 8,12 We found abundant, endogenous TG2 in capillaries grown in vitro (Figure 1), with enzyme activity localized in the HUVEC ECM. Inhibition of the endogenous TG2 had little effect on tube formation, suggesting that the observed in situ extracellular activity of TG2 is not essential for tube formation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been suggested that TG2-mediated ECM crosslinking in HUVEC and the endothelial-like cell line ECV304 contributes to basement membrane assembly and cell adhesion. 8,12 We found abundant, endogenous TG2 in capillaries grown in vitro (Figure 1), with enzyme activity localized in the HUVEC ECM. Inhibition of the endogenous TG2 had little effect on tube formation, suggesting that the observed in situ extracellular activity of TG2 is not essential for tube formation.…”
Section: Discussionmentioning
confidence: 90%
“…6 Many ECM proteins are known substrates of the enzyme, 7 and the crosslinking of these proteins by endothelial cell TG2 is thought to play a role in the stabilization of the basement membrane. 8 However, in a number of different tissues, inappropriate crosslinking of the ECM by TG2 following continuous tissue insult can lead to ECM accumulation and fibrosis. 9,10 Cell surface TG2 is also thought to be involved in cell migration, 11 and cell adhesion, 12 by a mechanism that is independent of its transamidating activity.…”
Section: Introductionmentioning
confidence: 99%
“…Cell surface TG2 crosslinks fibronectin, which acts to stabilize the ECM and anchor cells at the basement membrane (Martinez et al, 1994). TG2 binds with high affinity to fibronectin at the N-terminal 42-kDa gelatin binding domain of fibronectin via a novel recognition site within the NH 2 -terminal beta-sandwich domain of TG2 (Akimov and Belkin, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This could potentially result in a more resilient barrier at the blood-vessel interface. Other substrates, such as vitronectin (Sane et al, 1990), osteopontin (Prince et al, 1991), thrombospondin (Bale and Mosher 1986), fibronectin (Martinez et al, 1994), dermatan sulfate proteoglycan (Kinsella and Wight, 1990), and apo(a) (Borth et al, 1991), are often increased in the atheromatous plaque (Dufourcq et al, 1998;Giachelli et al, 1995;Hajjar and Nachman, 1996;Riessen et al, 1994;Shekhonin et al, 1987;Wight et al, 1985).…”
Section: Discussionmentioning
confidence: 99%